Applying Blooms Revised Taxonomy on Information and Communication Technology Skills of University Faculty Members - Manjunath Kamath; Anil Kumar (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: The goal of this research study is to stress on the Information and Communication Technology (ICT) skill of the University Faculty in the education/training sector. The study also focuses on Applying Bloom’s Taxonomy on Information and Communication Technology (ICT) Skill of University Faculty in achieving the goal of betterment in the education sector. Methodology: It also uses secondary data from well-known journals, popular websites, most read books, authorised reports and good conference proceedings. Findings: The very application of ICT has achieved outstanding results in achieving skill competencies in every field. This has encouraged the majority of people or the faculty community in particular to share, clarify and improve the content using Information technologies. Collaboration, conversation, and construction are the three theories upon which entire learning process success is expected. Research limitations/implications: This paper is fully based on secondary data from research articles available in search engines like Google scholar and Google search. Hence amount of work would have been good if primary data (which is difficult to collect) was collected and analysed. Originality/value: Past experiences have shown us that traditional teaching methodologies has some disadvantages, it is recommended that to solve those problems we should use Information Technologies available on the Internet. This study addresses the importance of higher order skills mentioned in top 4 layers in Bloom’s Taxonomy. Paper type: A case study paper.